Ranging patterns and factors associated with movement in free‐roaming domestic dogs in urban Malawi. Issue 1 (27th January 2022) - De la Puente‐Arévalo, María; Motta, Paolo; Dürr, Salome; Warembourg, Charlotte; Nikola, Christopher; Burdon‐Bailey, Jordana; Mayer, Dagmar; Lohr, Frederic; Gibson, Andy D.; Chikungwa, Patrick; Chulu, Julius; Gamble, Luke; et al.
Abstract: Rabies is a neglected zoonotic disease that causes around 59, 000 deaths per year globally. In Africa, rabies virus is mostly maintained in populations of free‐roaming domestic dogs (FRDD) that are predominantly owned. Characterizing the roaming behavior of FRDD can provide relevant information to understand disease spread and inform prevention and control interventions. To estimate the home range (HR) of FRDD and identify predictors of HR size, we studied 168 dogs in seven different areas of Blantyre city, Malawi, tracking them with GPS collars for 1–4 days. The median core HR (HR50) of FRDD in Blantyre city was 0.2 ha (range: 0.08–3.95), while the median extended HR (HR95) was 2.14 ha (range: 0.52–23.19). Multivariable linear regression models were built to identify predictors of HR size. Males presented larger HR95 than females. Dogs living in houses with a higher number of adults had smaller HR95, while those living in houses with higher number of children had larger HR95. Animals that received products of animal origin in their diets had larger HR95, and only in the case of females, animals living in low‐income areas had larger HR50 and HR95. In contrast, whether male dogs were castrated or not was not found to be associated with HR size. The results of this study may help inform rabies control and prevention interventions in Blantyre city, such as designing risk‐based surveillance activities or rabies vaccination campaigns targeting certain FRDD subpopulations. Our findings can also be used in rabies awareness campaigns, particularly to illustrate the close relationship between children and their dogs. Abstract : In Africa, rabies virus is mostly maintained in populations of free‐roaming domestic dogs (FRDD) that are predominantly owned. Characterizing the roaming behavior of FRDD can provide relevant information to understand disease spread and inform prevention and control interventions. In our study, we tracked with GPS collars 168 FRDD in Blantyre city, Malawi, to estimate their home range and identify predictors of HR size.